2009
DOI: 10.1093/toxsci/kfp102
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physiologically Based Biokinetic (PBBK) Modeling to Study Estragole Bioactivation and Detoxification in Humans as Compared with Male Rats

Abstract: The extent of bioactivation of the herbal constituent estragole to its ultimate carcinogenic metabolite 1′-sulfooxyestragole depends on the relative levels of bioactivation and detoxification pathways. The present study investigated the kinetics of the metabolic reactions of both estragole and its proximate carcinogenic metabolite 1′-hydroxyestragole in humans in incubations with relevant tissue fractions. Based on the kinetic data obtained a physiologically based biokinetic (PBBK) model for estragole in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
152
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(158 citation statements)
references
References 28 publications
5
152
0
1
Order By: Relevance
“…Those reactions were described well with Michaelis-Menten kinetics and the resulting Vmax and Km parameters were scaled to in vivo based on the microsomal or S9 protein content. The interplay of these multiple reactions was integrated in the PBBK model and the simulated concentrations of two estragole metabolites in the rat and human urine were reasonably consistent with the observed in vivo data considering the purpose of the modeling was to evaluate the dose-dependent changes in bioactivation, not to predict the absolute dose metrics (Anthony et al, 1987;Punt et al, 2008Punt et al, , 2009 (Paine et al, 1997). From the risk assessment point of view, other phase I and II enzymes in the GI tract should also be carefully considered in IVIVE.…”
Section: Example Of a Qivive Approach For Toxicity Of A Metabolitementioning
confidence: 78%
See 2 more Smart Citations
“…Those reactions were described well with Michaelis-Menten kinetics and the resulting Vmax and Km parameters were scaled to in vivo based on the microsomal or S9 protein content. The interplay of these multiple reactions was integrated in the PBBK model and the simulated concentrations of two estragole metabolites in the rat and human urine were reasonably consistent with the observed in vivo data considering the purpose of the modeling was to evaluate the dose-dependent changes in bioactivation, not to predict the absolute dose metrics (Anthony et al, 1987;Punt et al, 2008Punt et al, , 2009 (Paine et al, 1997). From the risk assessment point of view, other phase I and II enzymes in the GI tract should also be carefully considered in IVIVE.…”
Section: Example Of a Qivive Approach For Toxicity Of A Metabolitementioning
confidence: 78%
“…A couple of publications by Punt and colleagues (Punt et al, 2008(Punt et al, , 2009) present an example of a more sophisticated QI-VIVE approach using metabolism data collected in a number of subcellular fractions. Although the intent of the study was to evaluate the relevance of carcinogenicity of estragole reported in high-dose animal studies to human exposure situations, a similar QIVIVE approach also could be applied for the interpretation of in vitro toxicity assays.…”
Section: Example Of a Qivive Approach For Toxicity Of A Metabolitementioning
confidence: 99%
See 1 more Smart Citation
“…The average relative deviations between model predictions and experimental data were 36%, 49%, and 43% for TC, HDL-C, and non-HDL-C, respectively. This is considered successful within the present state-of-the-art of PBK modeling, where quantitative predictions may generally be correct within one order of magnitude (25)(26)(27)(28). These model predictions are generally within the experimental error margin given the small patient groups sizes (generally n < 20).…”
Section: Model Validationmentioning
confidence: 94%
“…For estragole that needs bioactivation to exert toxicity, detoxification of estragole 2¢, 3¢-oxides by epoxide hydrolases and glucuronidation of 1¢-hydroxyestragole would influence the toxicological effects [109,110]. Additionally, the formation of 1¢-oxoestragole is another important detoxification pathway of estragole in human [111]. Multiple herbal components might influence bioactivation of specific herbal ingredient through producing a significant impact on these competitive metabolism pathways.…”
Section: Competitive Detoxification Metabolism Pathwaysmentioning
confidence: 99%